Analisis Pembangunan Zona Integritas Wilayah Bebas Dari Korupsi Terhadap Kinerja Layanan Di KPKNL Jakarta II - Nisa, Nurvita Thoharotun; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
The development of the Corruption Free Area Integrity Zone (ZI-WBK) is a miniature implementation of bureaucratic reform in Indonesia. ZI-WBK development activities are implemented in government agencies with the aim of creating a bureaucratic work culture that is anti-corruption, high-performing, and able to provide quality public services. This study aims to determine the effect of ZI-WBK implementation on service performance at the Jakarta II State Assets and Auction Service Office (KPKNL). This study used a descriptive qualitative method with interviews conducted on KPKNL Jakarta II employees, participant observation, documentation studies, and questionnaires. The results of this study are that there is a positive influence from the implementation of ZI-WBK development activities on the performance of services provided to stakeholders. Various policies and innovations implemented while participating in ZI-WBK activities were able to improve service performance so that stakeholders felt very satisfied with the services they received.